SIFAT-SIFAT KOPAL MANILA DARI PEKALONGAN TIMUR DAN BANYUMAS BARAT - Yacob Ando; Bambang Wiyono (Jurnal Penelitian Hasil Hutan, 1988)
Manila  copal  is a  natural  rosin obtained by  tapping Agathis  trees. The  resin is generally  collected  every  other  two weeks.  In trade copal is known  of three kinds  namely: Caurry,  Congo, and Manila Copal. Indonesian  copal includes manila copal;  is divided   into  four  groups,   among  others: bua,  loba,  melengket, and  pontianak  copal.The  moisture  content   of  manila  copal from  East Pekalongan and West Banyumas  was 1.74%  and 1.85%; the colour, based on  the LPHH  standard  ranked  3 and  2;  impurities  2.47%  and 2.49%; softening  point  81°C and 92°C.;  ash content 0.04% and  0.08%; acid  number  118.93 and  139.71; saponification number 337.67  and 392.98;  and iod number  36.5  and 42.98,   repectively.Manila  copal from  East  Pekalongan  and  West Banyumas appeared  to have good  quality and  belongs  to  the first qualify   based  on  the  Indonesian Standard.  Manila copal  from  West Banyumas  has a  higher  resin acid content   then  that from East  Pekalongan.